(R*)-Methyl 2-(2,6-dimethoxy-3,5-dinitrobenzamido)propanoate - Xiaofei Li (Acta Crystallographica Section E, 2012)
In the title molecule, C13H15N3O9, the nitro groups are tilted with respect to the benzene mean plane by 22.8 (3) and 31.6 (3)°. The methoxy groups are in a cis orientation relative to the ring. In the crystal, molecules are linked by strong N—H...O hydrogen bonds into C(3) chains along [100].